Vroue in die Sinoptiese Evangelies – méér as dekoratiewe karakters - Dreyer, Yolanda (HTS teologiese studies, 2002)
Women in the Synoptic Gospels – more than decorative charactersThe aim of the paper is to show that the Synoptic Gospels represent different perspectives on Jesus and gender. From these perspectives Jesus’ narrated vision on the role of the male disciples and the women is described in order to explore some implications of the three visions in Mark, Matthew, and Luke. The focus is on developing a comprehensive philosophy which attests to the full humanity and personhood of women, the equal value of men and women as persons, and the public acknowledgement of their value. The paper demonstrates that gender studies in biblical interpretation can contribute not only to the special interests of women, but also in a broader sense to society as a whole.